Ultrasonic studies of Molecular interaction in the Ternary Liquid Mixtures of Acrylonitrile + Benzene + N Methyl Aniline at Different Temperatures. (2018) - Devi, R. Chithra; Mathammal, R.; Kesavasamy, R.; Rohini, V.
Abstract: The Density (ρ), Viscosity(η) and Ultrasonic velocity (U) in ternary liquid mixture of Acrylonitrile (AN) with benzene in N-methyl aniline have been measured at 303K, 308K and 313K respectively, over the entire composition range using an ultrasonic interferometer at 2MHz frequency. From the experimental data various acoustical and thermo dynamical parameters such as; adiabatic compressibility(β), intermolecular free length(Lf ), acoustic impedance(Z), free length and free volume have been computed using standard relations. The results have been analyzed on the basis of variation in thermodynamic parameters. These parameters are found to be very sensitive in exploring the interaction between the component molecules, which gives a better understanding of the liquid mixtures. The results have been interpreted in terms of dipole induced dipole interaction.